Global Da’wa Revitalization through Spiritual Values in Local Wisdom - Bachtiar, M. Anis (Proceedings of International Conference on Da'wa and Communication, 2019)
This paper seeks to elaborate the implementation of Da'wa so that the objectives of Da'wa can be achieved to the maximum. There needs to be an innovative and creative missionary revitalization effort carried out by a preacher as an implementer of Da'wa, including utilizing local wisdom products to support the success of Da'wa . Among the local wisdom products that can be adopted by a preacher is the behavior of penance which is usually done by the Javanese community. The practice of penance was initially carried out by asceticism, fasting at certain times was finally baptized with Islamic values to do certain activities such as fasting, reducing food to purify the form, reducing sleep to reduce feelings and feelings and preventing sahwat to purify power. penance in life is an effort to get closer to God, both in attitude, behavior, soul, and mind. Tirakat can be seen as a spiritual effort from an individual, in the form of body and soul concern in achieving something by drawing closer to God. One form of getting closer to God is by fasting. The preacher as the messenger must meet some minimum criteria as a preacher among the kretria of the preacher is noble. In order to realize the noble character of a preacher must be diligent in doing penance, because it contains an increase in self control and spirituality. Thus a preacher besides delivering his preaching verbally, a preacher will also give uswah hasanah and of course the preaching delivered gets optimal results.